Gene RRN4 in Saccharomyces cerevisiae encodes the A12.2 subunit of RNA polymerase I and is essential only at high temperatures. - Nogi, Y (1993)
We have previously isolated mutants of Saccharomyces cerevisiae that are primarily defective in transcription of 35S rRNA genes by RNA polymerase I and have identified genes (RRN1 to RRN9) involved in this process. We have now cloned the RRN4 gene by complementation of the temperature-sensitive phenotype of the rrn4-1 mutant and have determined its complete nucleotide sequence. The following results demonstrate that the RRN4 gene encodes the A12.2 subunit of RNA polymerase I. First, RRN4 protein expressed in Escherichia coli reacted with a specific antiserum against A12.2. Second, amino acid sequences of three tryptic peptides obtained from A12.2 were determined, and these sequences are found in the deduced amino acid sequence of the RRN4 protein. The amino acid sequence of the RRN4 protein (A12.2) is similar to that of the RPB9 (B12.6) subunit of yeast RNA polymerase II; the similarity includes the presence of two putative zinc-binding domains. Thus, A12.2 is a homolog of B12.6. We propose to rename the RRN4 gene RPA12. Deletion of RPA12 produces cells that are heat but not cold sensitive for growth. We have found that in such null mutants growing at permissive temperatures, the cellular concentration of A190, the largest subunit of RNA polymerase I, is lower than in the wild type. In addition, the temperature-sensitive phenotype of the rpa12 null mutants can be partially suppressed by RPA190 (the gene for A190) on multicopy plasmids. These results suggest that A12.2 plays a role in the assembly of A190 into a stable polymerase I structure.